Improving the relationships between Indigenous rights holders and researchers in the Arctic: an invitation for change in funding and collaboration. (1st June 2022) - Doering, Nina; Dudeck, Stephan; Elverum, Shelly; Fisher, Charleen; Henriksen, Jan Erik; Herrmann, Thora Martina; Kramvig, Britt; Laptander, Roza; Milton, Justin; Omma, Elle Merete; Saxinger, Gertrude; Scheepstra, Annette J M; et al.
Abstract: Truly transdisciplinary approaches are needed to tackle the complex problems that the Arctic is facing at the moment. Collaboration between Indigenous rights holders and researchers through co-creative research approaches can result in high-quality research outcomes, but crucially also address colonial legacies and power imbalances, enhance mutual trust, and respect the rights of Indigenous Peoples. However, to be successful, collaborative research projects have specific requirements regarding research designs, timeframes, and dissemination of results, which often do not fit into the frameworks of academic calendars and funding guidelines. Funding agencies in particular play an important role in enabling (or disabling) meaningful collaboration between Indigenous rights holders and researchers. There is an urgent need to re-think existing funding-structures. This article will propose a new paradigm for the financing of Arctic research, which centres around the inclusion of Indigenous partners, researchers, and institutions from the initial planning stages of funding programmes to the final stages of research projects. These findings and recommendations have been contextualized based on critical reflections of the co-authors, a group of Indigenous and non-Indigenous partners, who have practiced their own collaborative work process, the challenges encountered, and lessons learned.